Analisis LKPD Pembuatan Kompos Berbasis ESD-TPACK untuk Meningkatkan Sikap Ilmiah Peserta Didik - Salsabila, Ainus; Suyono, Suyono; Supardi, Zainul Arifin Imam (Universitas Negeri Jakarta, 2025)
This research aims to develop teaching materials in the form of Student Worksheets based on ESD (Education for Sustainable Development) and TPACK (Technological Pedagogical Content Knowledge) that focus on improving students' scientific attitudes in biology learning. The identified problem is the lack of teaching materials relevant to sustainability issues and the suboptimal integration of technology in learning. This research uses the ADDIE development design, which includes needs analysis, design, development, implementation, and evaluation of teaching materials. Validation was conducted by media experts and education practitioners to ensure the product's validity. The validation results show that the ESD-TPACK-based student worksheet device has an average validity score of 0.96, categorized as very valid, and a reliability score of 0.98. This student worksheet trains four aspects of scientific attitudes, namely determinism, the belief that every problem has a solution, curiosity, and empathy towards human conditions. The application of this student worksheet is expected to enhance students' critical thinking skills and sense of responsibility towards environmental issues through project-based active learning. In conclusion, the ESD-TPACK-based student worksheets are valid and suitable for supporting sustainable learning and enhancing students' scientific attitudes in the context of biology education.